Can I have a Stegosaurus, Mom? Can I? Please!? - Grambling, Lois G.; Lewis, H. B. (Mahwah, N.J. : BridgeWater Books, 1994)
A child describes all the possible advantages of having a Stegosaurus for a pet.
8 9 13 21 23 30
Keywords: Stegosaurus -- Fiction; Dinosaurs -- Fiction